Beethoven's Diabelli Variations - Kinderman, William (New York Oxford University Press, 1989)
Beethoven's Thirty-Three Variations on a Waltz by Diabelli, his longest and most complex piece for piano, stands beside the Ninth Symphony, the Missa Solemnis, and the late quartets as one of the monumental achievements of his last period. In this first extended study of these variations, William Kinderman investigates their compositional origins and explores them in the context of Beethoven's other works of this time. Kinderman shows how the composer transforms, parodies, and ultimately transcends Diabelli's commonplace waltz in a fascinating series of historical allusions to other composers in the final variations. Kinderman's discussion provides considerable insight into Beethoven's working methods and illuminates the structure of the finished work, and ultimately the nature of the creative process itself. This new reissue of Kinderman's classic text includes a free CD of his celebrated recording of the Diabelli Variations, described by Andras Schiff as "a very vivid sounding experience."
Keywords: Beethoven, Ludwig van -- 1770-1827; Diabelli, Anton -- 1781-1858; 19th Century (1801-1900); Theme and variations; Keyboard music; Piano; Waltz; Vienna (Austria)